Clinical Outcomes and Quality of Life of Patients with End-Stage Chronic Kidney Disease following Advance Care Planning in the Community - Pechrampanao, Yanipit; Panthonglang, Warissara; Bonkhunthod, Punnathut (Disease Control Journal, 2026)
This participatory action research aimed to: 1) examine the situation and problems in caring for patients with end-stage chronic kidney disease in the community; 2) develop an advance care planning (ACP) process appropriate to the local context; and 3) evaluate the effects of the model on clinical outcomes, quality of life, and treatment decision-making. The sample consisted of 20 patients. Data were collected between January and April 2025. Research instruments included a demographic questionnaire, a quality-of-life assessment, and a clinical outcomes record form. Quantitative data were analyzed using descriptive statistics and compared before and after the intervention using paired t-test, while qualitative data were analyzed using content analysis. The results revealed that the existing care system had limitations in service structure, resource allocation, and multidisciplinary communication. After implementing the ACP process, patients demonstrated clearer treatment decision-making. The proportion of patients choosing palliative care increased from 30.0% to 56.7%, while those choosing renal replacement therapy decreased from 70.0% to 43.3%. Clinical outcomes showed significant reductions in systolic and diastolic blood pressure (p=0.010 and 0.019 respectively) and serum potassium levels, along with a significant increase in hematocrit levels (p=0.005 and 0.001respectively). Additionally, the proportion of patients receiving erythropoietin increased from 2.9% to 38.2%. Quality of life significantly improved, with overall scores increasing (p=0.003). Scores related to disease burden, symptoms, and the impact on daily life significantly decreased (p<0.001, 0.028 and <0.001 respectively). In conclusion, the participatory ACP process effectively enhanced informed treatment decision-making and led to significant improvements in clinical outcomes and quality of life among patients with end-stage chronic kidney disease in the community.